Characteristics, distribution, source apportionment, and potential health risk assessment of polycyclic aromatic hydrocarbons in urban street dust of Kerman metropolis, Iran. Issue 6 (2nd November 2019) - Abbasnejad, Behnam; Keshavarzi, Behnam; Mohammadi, Zargham; Moore, Farid; Abbasnejad, Ahmad
ABSTRACT: In this study, the concentrations of street dust-bound polycyclic aromatic hydrocarbons (PAHs) in Kerman metropolis as a typical arid urban area were determined to investigate the contamination, molecular composition, toxicity, and sources of PAHs. Sixteen individual PAHs on the United States Environmental Protection Agency priority list were analyzed using gas chromatography-mass spectrometry in street dust samples from 30 sites. ∑PAHs ranged between 165 and 5314.7 µg·kg −1 with a mean of 770.8 µg·kg −1 . The most abundant individual PAHs were fluoranthene, phenanthrene, pyrene, and chrysene, respectively. High molecular weight PAHs (4-6 rings) made 74.8% of ∑PAHs mass and were dominant in all sites. Source apportionment was performed using ring classification, diagnostic ratios, and principal component analysis-multiple linear regression. The results indicated that primary contributors of PAHs in the street dust of Kerman could be liquid fossil fuel combustion, natural gas combustion, and petrogenic sources, accounting for 82.4%, 11.5%, and 6.1%, respectively. The calculated incremental lifetime cancer risk is 8.13 × 10 −4 for children and 6.27 × 10 −4 for adults. Hence, both children and adults in Kerman are potentially exposed to a high carcinogenic risk via ingestion and dermal contact.